PIM research informs the renewal of community forest concessions in the Maya Biosphere Reserve (Guatemala) - CGIAR Research Program on Policies, Institutions, and Markets (2019)
Joint FTA and PIM research highlighted the socio-economic benefits from 12 community forest concessions in the Maya Biosphere Reserve in Petén, Guatemala. These findings contributed to the revision of the norms for granting concessions and the renewal of the concession contract for one of the community forest cooperatives, with the other ones expected to follow in 2020.